Pengaruh Edukasi Toilet Training Terhadap Kemandirian Dalam Melakukan Toilet Training Usia 5-6 Tahun Di TK Yayasan Mutiara Hati Kelurahan Manyaran Semarang Barat - Fetti Nur Diyanti; Sri Hartini MA; Anis Ardiyanti (STIKes Ibnu Sina Ajibarang, 2023)
Background: Toilet training is an exercise to control the urination and defecation of children and to develop their directedness. Self-directedness refers to an individual attitude to act freely with personal motivation without other individual assistance. Objective: This research determined the influence of toilet training education toward the self-directedness to carry out toilet training for children aged between 5 and 6 years at Kindergarten of Mutiara Hati Foundation, Manyaran village, Western Semarang. Research design: this pre-experimental research applied one group pretest-posttest design and quantitative description. The sample consisted of 30 respondents taken with total sampling. Research results: most respondents were males, 53%; the age of learning toilet training was mostly pre-school aged, 66.7%; the pretest-posttest result of the self-directedness was 100%. The Wilcoxon test obtained a p-value of 1.000 higher than 0.05, indicating no significant influence of toilet training toward self-directedness to promote toilet training for children aged between 5 and 6 years old. Conclusion: self-directedness of children between 5 and 6 years old to practice toilet training. Toilet training is not affected by education at that age. Suggestions: The researcher suggests researchers take respondents aged between 2 and 4 years old without self-directedness of practicing toilet training.